Observation of a narrow pentaquark state, Pc(4312)+, and of the two-peak structure of the Pc(4450)+ - Aaij, Roel; D'Argent, Philippe; Bachmann, Sebastian; Berninghoff, Daniel; Borsato, Martino; Braun, Svende; Comerma-Montells, Albert; Dziewiecki, Michal; Gerick, David; Grabowski, Jascha; Han, Xiaoxue; Hansmann-Menzemer, Stephanie; et al. (Physical review letters, 2019)
A narrow pentaquark state, Pc(4312)+, decaying to J/ψp, is discovered with a statistical significance of 7.3σ in a data sample of Λ0b→J/ψpK− decays, which is an order of magnitude larger than that previously analyzed by the LHCb Collaboration. The Pc(4450)+ pentaquark structure formerly reported by LHCb is confirmed and observed to consist of two narrow overlapping peaks, Pc(4440)+ and Pc(4457)+, where the statistical significance of this two-peak interpretation is 5.4σ. The proximity of the Σ+c¯D0 and Σ+c¯D*0 thresholds to the observed narrow peaks suggests that they play an important role in the dynamics of these states.